A measurement-based path loss model for wireless links in mobile ad-hoc networks (MANET) operating in the VHF and UHF band - Fischer, Jörg Dieter; Heuberger, Albert; et al. (Proceedings IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, 2012)
For the development of future mobile-to-mobile communication systems, realistic channel models are required. Available models are aiming at broadcasting applications using high antenna towers and are therefore not applicable for mobile-to-mobile applications like mobile ad-hoc networks (MANET). In this paper, measurements of the path loss using car-mounted receiver and transmitter antennas are presented. Based on the measurement results, a new path loss model is proposed. It is shown that this model provides a more realistic prediction of the path loss for MANET systems in the VHF and UHF band than the widely used Okumura-Hata model. © 2012 IEE
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.komele.ameasu

Analysis of Average Outage Probabilities in a Finite, Centralised Radio Network with Slotted Random Access - Lieske, Hendrik; Beer, Frederik; Fischer, Jörg Dieter; Kilian, Gerd; Robert, Jörg; Heuberger, Albert (Proceedings of 2014 European Conference on Smart Objects, Systems and Technologies (SmartSysTech), 2014)
The paper analyses the outage probability of a radio node in a finite size large-scale data aggregation network which employs slotted random medium access. In most literature, this performance metric is usually derived from a Poisson point process distribution of radio nodes in infinite space. In contrast, we analyse a network with finite area and a fixed number of interfering nodes using a binomial point process. Based on the point process, conditional outage probabilities in a log-normal fading channel in case of n interferers are derived. These interim results are used to obtain the outage probability of a desired radio node as a function of the offered network load. We present numerical outage probabilities for distinct path loss exponents, capture thresholds and varying distances between node and receiver.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.komele.analys
Keywords: Binomial point process; Cochannel interference; Wireless networks

A Novel Delay Spread Distribution Model for VHF and UHF Mobile-to-Mobile Channels - Fischer, Jörg Dieter; Heuberger, Albert; et al. (European Conference on Antennas and Propagation (EuCAP), 2013)
In this paper, the delay spread distribution of the mobile-to-mobile channel for various environments is analyzed based on new measurements in the frequency band from 30 MHz to 400 MHz. The results of the distribution are compared to the literature. In order to make the measurement results accessible for a simulation-based system design process, a new delay spread distribution model is proposed. This new model allows realistic estimates for the design and evaluation of mobile-to-mobile communication systems. © 2013 EurAA
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.komele.anovel

A Stochastic Geometry Approach to Model the Shadow Fading for Mobile Ad-Hoc Networks - Fischer, Jörg Dieter; Beer, Frederik; Lieske, Hendrik; Robert, Jörg; Thielecke, Jörn; Heuberger, Albert (Wireless On-Demand Network Systems and Services (WONS), 2013)
This paper deals with the problem of modeling shadow fading for wireless links in mobile ad-hoc networks (MANET). In contrast to broadcasting or cellular applications, the links in a MANET generally cannot be analyzed indepen-dently. Thus the evaluation of routing techniques and network protocols for future systems requires a realistic modeling of the correlation of the links. In the following a novel modeling approach based on stochastic geometry will be presented. This computationally inexpensive model allows for dual mobility, the simultaneous movement of the transmitter and the receiver, and can be easily adapted for various environments. The model can be integrated in network simulators and therefore enables the analysis of the influence of shadow fading on the performance of MANET routing algorithms and protocols. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.komele.astoch

Modeling Shadow Fading for Mobile-to-Mobile Communications in the VHF and UHF Band. - Fischer, Jörg Dieter; Grossmann, Marcus; Felber, Wolfgang; Landmann, Markus; Heuberger, Albert (Proceedings IEEE International Conference on Wireless Information Technology and Systems, 2012)
Measurements of the shadow fading characteristics in tactical communication scenarios have been presented. New parameter sets for widely used shadow fading models have been proposed. Modeling the shadow fading using these parameter sets, rather than the parameters obtained through measurements with high antenna setups, will result in a more realistic representation of the phenomenon for communication systems with car-mounted Rx and Tx antennas. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.komele.modeli

NATO tactical narrowband waveform: development and performance of functional software - Fischer, Jörg Dieter; Heuberger, Albert; et al. (Military Communications and Information Systems Conference MCC 2009, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.komele.natota

On the Importance of Realistic Correlated Shadow Fading Modeling for Mobile Ad-Hoc Networks - Fischer, Jörg Dieter; Beer, Frederik; Lieske, Hendrik; Robert, Jörg; Thielecke, Jörn; Heuberger, Albert (International Symposium on Computing and Networking (CANDAR) 2013, 2013)
The simulation of typical network scenarios is essential for the evaluation of design proposals for future mobile adhoc network (MANET) systems. In this paper, we demonstrate the importance of realistic correlated shadow fading modeling for this application. This is done by simulating a basic mobile network scenario and comparing the estimated outage probability values for an uncorrelated link model and a more realistic correlated link model to the results of real world measurements. The simulations show that the use of a shadow fading model, which does not consider the correlation between the links in a network, results in significant estimation errors. The stochastic geometry shadowing model, which incorporates the link correlation, is able to provide a much more realistic estimate. Using this correlated model rather than the models currently in use will help to avoid flawed design decisions which would affect future systems. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.komele.onthei

Performance of Multi-User Detection in Systems with Multiple Antennas for OFDM-based Radio Communication - Fischer, Jörg Dieter (2005)

Wireless Communication Systems Design for Tactical Software-Defined Radios - From Scenario-Based Analysis to Channel and Waveform Parameter - Fischer, Jörg Dieter; Heuberger, Albert; et al. (RTO-MP-IST-092 - Military Communications and Networks, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.komele.wirele